The Varieties of reference: Gareth Evans - Macdowell, John (Oxford Clarendon Press, 1982)
Gareth Evans, one of the most brilliant philosophers of his generation, died in 1980 at the age of thirty-four. He had been working for many years on a book about reference, but did not complete it before his death. The work was edited for publication by John McDowell, who contributes a Preface.